2011
DOI: 10.1111/j.1479-828x.2011.01318.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in pregnancy rate by removal of cervical discharge prior to embryo transfer in ICSI cycles: A randomised clinical trial

Abstract: Removal of cervical discharge prior to ET may have a significant effect on the rate of implantation, pregnancy and live birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The role of the procedure was much more evident before embryo transfer during intracytoplasmic sperm injection (ICSI) cycles. Moini et al reported a clinical pregnancy rate of 39.2% in the intervention group compared with 22.6% in the control group ( P < 0.001; OR, 2.297; CI 95%, 1.552–3.399), while another two studies reported a similar increase in pregnancy rates when they removed the mucus by cytobrush followed by vigorous cervical canal irrigation. Eskander et al also found a 2.18‐fold increase in pregnancy rates with cervical mucus aspiration prior to embryo transfer.…”
Section: Discussionmentioning
confidence: 97%
“…The role of the procedure was much more evident before embryo transfer during intracytoplasmic sperm injection (ICSI) cycles. Moini et al reported a clinical pregnancy rate of 39.2% in the intervention group compared with 22.6% in the control group ( P < 0.001; OR, 2.297; CI 95%, 1.552–3.399), while another two studies reported a similar increase in pregnancy rates when they removed the mucus by cytobrush followed by vigorous cervical canal irrigation. Eskander et al also found a 2.18‐fold increase in pregnancy rates with cervical mucus aspiration prior to embryo transfer.…”
Section: Discussionmentioning
confidence: 97%
“…A systematic review was unable to make a definitive conclusion on this topic, which was limited by the inclusion of an abstract that was never subsequently published and a study using the cytobrush (69). Therefore, data from the only well-designed RCT (N¼530) and a prospective, controlled cohort study (N¼286) were used for the recommendation (66,67). The RCT showed improved clinical pregnancy rate (39.2% study vs 22.6% controls, P< .001) and live-birth rate (33.6% study vs 17.4% controls, P< .001) with the removal of cervical mucus (66).…”
Section: Summary Statementsmentioning
confidence: 99%
“…[17][18] Moreover, the diversity of the organisms that comprise the vaginal microbial community varies among women. [19] Since, the lower genital tract is naturally inhabited with vaginal flora, and pathogenic organisms, operative procedures through the genital tract may lead to moderate to high risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…[14,15] Although, Shrimali et al, suggested that the cervical mucus may trap the embryos, and facilitate their expulsion during catheter withdrawal. [16] Visschers et al, concluded that it is unlikely that removal of cervical mucus prior to embryo transfer has a significant effect on live birth rates [20] , and this study also concluded that the presence of blood and/or mucus in the embryo transfer catheters did not affect the clinical pregnancy rates.…”
Section: Eskandar Et Al Andmentioning
confidence: 99%
See 1 more Smart Citation